MEMBALIKKAN PROSES PENUAAN LEWAT MANIPULASI PROGRAM BIOENERGI DALAM HYPOTHALAMUS - Effendi, Irwan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Is the aging process something that all humans should experience? Or is there a way to reverse the process so that aging humans can get back young? We know that after birth, humans go through stages as babies, then become children, teenagers, adults, age, and eventually die. The question is, how can our bodies know when it's time to move on to the next stage? Why does the average human being go from adolescence to physical maturity in their teens and not at 40? This study tested whether these stages can be reversed by making modifications to the Bioenergy program stored in the Hypothalamus, with the aim of making the body think that the stages being undergone are stages from adolescence to adulthood and thus adjusting their conditions. This study was held in two waves and so far, although it is far from perfect, the results obtained by the participants are significant enough to state that the method used is correct and only needs improvement or merging with other methods.